2006
DOI: 10.1093/mutage/gel054
|View full text |Cite
|
Sign up to set email alerts
|

The stimulatory role of human cytochrome b5 in the bioactivation activities of human CYP1A2, 2A6 and 2E1: a new cell expression system to study cytochrome P450-mediated biotransformation (a corrigendum report on Duarte et al. (2005) Mutagenesis 20, 93-100)

Abstract: This corrigendum report describes the study of the comparison of human cytochrome b(5) (b(5)) with rat b(5) when coupled with human cytochrome P450 CYP1A2, 2A6 or 2E1. Results indicate a role of the N-terminal part of b(5) in the coupling with CYP. Indeed, the plasmid pLCM-b(5)-RED used in our former study on b(5) [Duarte et al. (2005) Mutagenesis, 20(2), 193-100] erroneously contained rat b(5). Plasmid pLCM-b(5)-RED was corrected with human b(5) and subsequently all experimental work was repeated as was descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…As such, any difference detected in the CYP activities can be ascribed to differences in the CPR mut :CYP coupling. Indeed, the CPR:CYP stoichiometries measured in membrane fractions were similar to those described previously for the BTC system in our former studies [11,16,33,[36][37][38][39], and comparable with the ranges of those reported for human liver microsomes, which range from 1:2 to 1:13 [40,41]. These ratios evidence a submolar presence of CPR vs. CYP, which is recapitulated in the BTC system, as already demonstrated in our former studies [11,22,36,39].…”
Section: Characterization Of the Membrane Fractionssupporting
confidence: 91%
See 2 more Smart Citations
“…As such, any difference detected in the CYP activities can be ascribed to differences in the CPR mut :CYP coupling. Indeed, the CPR:CYP stoichiometries measured in membrane fractions were similar to those described previously for the BTC system in our former studies [11,16,33,[36][37][38][39], and comparable with the ranges of those reported for human liver microsomes, which range from 1:2 to 1:13 [40,41]. These ratios evidence a submolar presence of CPR vs. CYP, which is recapitulated in the BTC system, as already demonstrated in our former studies [11,22,36,39].…”
Section: Characterization Of the Membrane Fractionssupporting
confidence: 91%
“…The characterization of contents of heterologous expressed proteins found in the membrane fractions (isolated using the bacterial CPR/CYP co-expression system, BTC) [22,36] containing the wildtype CPR (CPR wt ) and mutant CPRs (CPR mut ) combined with CYP1A2, 2A6 or 3A4 is shown in Table 1. Co-expression of CPR mut with CYP1A2, 2A6, or 3A4 was achieved with a stoichiometry approximating the one obtained with CPR wt for each CYP, demonstrating no significant differences (p > 0.05).…”
Section: Characterization Of the Membrane Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, this simple cell-model demonstrated the co-expression of CYPOR with human CYPs (including CYP1A2), via a bi-plasmid system [15]. The two human proteins are correctly expressed, membraneanchored and are fully active, reflecting in vivo activities and representing the stoichiometry of the membrane-bound enzyme complex in the endoplasmic reticulum [16]. This is of importance, as exaggerated CYPOR:CYP ratios (≥ 2) lead to irrelevant enzyme kinetics and, thus, cell models containing such relative expression levels are not representative for studying the effects of ABS-CYPOR mutants on CYP activity.…”
Section: Introductionmentioning
confidence: 99%
“…δ-Aminolaevulinic Acid (5-ALA) is the first committed intermediate of the heme biosynthesis pathway in vivo , and ferric citrate can provide ferrous iron for this pathway as well as heme for the baculovirus/ sf9 system. POR should be taken into consideration for P450s heterologous expression because POR content is rate-limiting for CYP reactions[9]. Previous studies showed that functional CYP450s could be obtained by adding cofactors ( e.g.…”
Section: Introductionmentioning
confidence: 99%